2011
DOI: 10.1007/s00520-011-1094-z
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine use and assessment of quality of life in Korean breast cancer patients: a descriptive study

Abstract: A significant number of patients with breast cancer have used CAM, and health care providers should be aware of the variety of CAM methods and their patients' CAM uses for the proper management of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
69
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 41 publications
6
69
0
4
Order By: Relevance
“…This result is also similar to the study done in German, where the most prominent sources of information for CAM choice were outside the medical community and included families, relatives, and friends (49%) [33]. However, few other studies reported media such as internet, television, radio, newspapers, and magazines as the main information source about CAM [34,35]. To prevent the abuse of CAM, health care providers should have open discussion with their patients about CAM use and provide appropriate information on the safety and efficacy of CAM therapies.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This result is also similar to the study done in German, where the most prominent sources of information for CAM choice were outside the medical community and included families, relatives, and friends (49%) [33]. However, few other studies reported media such as internet, television, radio, newspapers, and magazines as the main information source about CAM [34,35]. To prevent the abuse of CAM, health care providers should have open discussion with their patients about CAM use and provide appropriate information on the safety and efficacy of CAM therapies.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, CAM use was discussed with their physicians by only 20.8% of patients using CAM. This is comparable to the 32.7% reported in an earlier study of Korean cancer patients and 29.6% in Malaysian patients with cancer [32,34]. However, it is much lower than the 71% reported by breast cancer patients in USA [36].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similarly, Molassiotis et al 8 reported that 4.4% of patients in their study experienced adverse effects from CAM use. Kang et al 42 , in a recent study, determined 34.7% of patients were happy, 68.8% moderately happy, 2.5% unhappy, and 6.5% had adverse effects from CAM use.…”
Section: Discussionmentioning
confidence: 98%
“…즉, 한방요법 이외의 보완대체요법에 대한 국민의 인식도 상당히 긍정적이므로 전체 국민의 74.8%가 1년 동안 적어도 1회 이상 이용한 경험이 있었다 [11]. 이렇듯 우리나라에서는 건강 증진 [12] 외에도 당뇨병 [13], 뇌졸중 [14,15], 암 [16][17][18][19], 골관절염 [20], 만성통증 [21] (Table 4, Table 5). (Table 7).…”
unclassified